The role of estimated muscle power from a sit-to-stand test in determining frailty in community-dwelling older adults - Cillin Condon; Eleanor Fallon; Fearghal P. Behan; Roman Romero-Ortuno; Seán McAuliffe (PLoS ONE, 2026)
Introduction This study explored the usefulness of estimated lower-limb muscle power, derived from the 5-times sit-to-stand (5xSTS) test, for identifying frailty among community-dwelling older adults in Ireland. Methods Data from Wave 3 of The Irish Longitudinal Study on Ageing (TILDA) were analysed, focusing on adults aged 50 years and older. Muscle power was estimated using a standardised equation from the five-time sit-to-stand (5xSTS) test, incorporating body height, mass, and chair height. Frailty status was classified using an Index, according to established criteria. Logistic regression models assessed the predictive capacity of muscle power relative to 5xSTS. Thresholds for frailty risk were explored through Receiver Operating Curves and Locally Weighted Scatterplot Smoothing. Results Findings reveal a decline in muscle power with advancing age, more pronounced in females and frail individuals. Muscle power estimates showed moderate agreement with frailty status, with sensitivity and specificity comparable to those of the 5xSTS. Muscle power less than 2.5 Watt·kg - ¹ in males and 2.08 Watt·kg - ¹ in females was associated with increased frailty risk, consistent with other studies. Overall power estimation showed a predictive performance similar to that of traditional assessments such as Timed Up and Go, supporting its utility in clinical and community settings. Conclusion Estimated muscle power derived from the 5xSTS test is a practical, reliable tool for early identification of frailty among older adults. Its accessibility and predictive validity suggest it could complement existing clinical assessments but not replace them.